Bio Coating Based on Damar Resin on Mild Steel in Corosive Media (Acid Effect) by Using Silica from Rice Husk Extract (Universitas Negeri Semarang, 2021)
Bio coating is a natural anti-corrosion material that can be easily degraded and renewed. Rice husk extract and damar resin are alternative natural materials that are believed to have a relatively high silica content, so they can be used as a substitute for synthetic chemicals to protect metals from corrosion. This research was conducted to determine the bio-coating ability of mild steel in H2SO4 corrosive media. The object of the experiment used rice husk waste and damar resin as the primary raw materials. The analytical method used is the weight loss method. The resin sap and silica sol obtained from the ashing of rice husks are mixed to form a homogeneous product. Metal samples coated with bio-coating material are immersed in 0.5 M sulfuric acid solution, with variations in silica concentrations of 500, 1000, 1500 ppm, 1, 2, and 3 hours, and at temperatures of 40, 60, and 80°C, which is then tested for the ability of the bio coating material. The results show that the higher the temperature and the longer the immersion time, the corrosion rate on the metal increases. The variation of the 1500 ppm silica concentration shows better efficiency results than other concentrations at a temperature of 40°C for an immersion time of 1 hour.